Role of Vibrio cholerae neuraminidase in the function of cholera toxin. - Galen, J E (1992)
Vibrio cholerae neuraminidase (NANase) is hypothesized to act synergistically with cholera toxin (CT) and increase the severity of a secretory response by increasing the binding and penetration of CT to enterocytes. To test this hypothesis, the NANase gene (nanH) from V. cholerae Ogawa 395 was first cloned and sequenced. Isogenic wild-type and NANase- V. cholerae 395 strains were then constructed by using suicide vector-mediated mutagenesis. The influence of NANase on CT binding and penetration was examined in vitro by using culture filtrates from these isogenic strains. Fluorescence due to binding of fluorescein-conjugated CT to C57BL/6 and C3H mouse fibroblasts exposed to NANase+ filtrates increased five- and eightfold, respectively, relative to that with NANase- filtrates. In addition, NANase+ filtrates increased the short-circuit current measured in Ussing chambers 65% relative to that with NANase- filtrates, although this difference decreased as production of CT increased. The role of NANase in V. cholerae pathogenesis was examined in vivo by intragastric inoculation of the isogenic strains into CD1 suckling mice. No difference in fluid accumulation ratios was seen at doses of 10(4) to 10(8) CFU, but NANase+ strains produced 18% higher fluid accumulation ratios at 10(9) CFU than NANase- strains when inoculated into nonfasted suckling mice. It is concluded that NANase plays a subtle but significant role in the binding and uptake of CT by susceptible cells under defined conditions.